Implementation of Kpopfication in the campaign of presidential candidate Anies Rasyid Baswedan - Fikrani Deslia, Iva; Rafika Sari, Zahroh (COMMICAST, 2024)
The digital era makes the existence of social media a tool used to spread and get information about many things that happen from one individual to another with a wider scope. This is also the basis for the entry of many cultures from other countries through posts spread through social media. The Korean cultural wave, also known as Hallyu, is a term used in the process of spreading Korean culture through products from South Korea. With a successful team, Anies Rasyid Baswedan utilized interest generation with a K pop design platform similar to the idol concept to communicate with his fans. Through the main X (Twitter) account @aniesbubble, he forms a positive image with the information shared. The research method used in this research is descriptive qualitative. The study aims to of this research entitled Implementation of Kpopfication in the Campaign of Presidential Candidate Anies Rasyid Baswedan is to find out the implementation of Kpopfication in the campaign of Presidential candidate Anies Baswedan and find out the impact of using Kpopfication in the campaign strategy. The results of this study show that the implementation of Kpopfication used in the campaign of Anies Baswedan's presidential candidate is by using the X application which is designed according to the fansite account of the bubble application which reports a lot of information using Korean. In addition, the @aniesbubble account also utilizes the habits of Kpopers such as live reports of activities, production fan projects, and distributing free goods. The impact of kpopfication carried out by the @aniesbubble account is that many people are interested in following and deciding to elect Anies Baswedan as president for the next period. From the creative campaign strategy Anies Baswedan received 24.95 votes.